STUDI TENTANG PERAN MASYARAKAT ADAT TERHADAP KELESTARIAN HUTAN ADAT KENEGERIAN RUMBIO KECEMATAN KAMPAR KABUPATEN KAMPAR - Sandi, Ari; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the importance of the role of indigenous peoples in maintaining the sustainability of indigenous forest of kenegerian Rumbio Kampar district of Kampar regency. In relation to that the authors take the title of research,